(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article covers the role and importance of parenting in the upbringing of a boy. As a role model, the issues of how the father affects the boy, teaching responsibility and hard work, the formation of discipline and order, the development of self-confidence and masculine qualities, as well as emotional support are analyzed. The article also shows the importance of the relationship between father and son.